Artificial Aurora Experiments and Application to Natural Aurora - Mishin, Evgeny V. (Frontiers in Astronomy and Space Sciences, 2019)
A review is given of the effects observed during injections of powerful electron beams from sounding rockets into the upper atmosphere. Data come from in situ particle and wave measurements near a beam emitting rocket and ground-based optical, wideband radiowave, and radar observations. The overall data cannot be explained solely by collisional degradation of energetic electrons but require collisionless beam plasma interactions (BPI) be taken into account. The beam-plasma discharge theory describes the features of the region near a beam-emitting rocket, where the beam-excited plasma waves energize plasma electrons, which then ignite the discharge. The observations far beneath the rocket reveal a double-peak structure of artificial auroral rays, which can be understood in terms of the beam-excited strong Langmuir turbulence being affected by collisions of ionospheric electrons. This leads to the enhanced energization of ionospheric electrons in a narrow layer termed the plasma turbulence layer (PTL), which explains the upper peak. Similar double-peak structures or a sharp upper boundary in rayed auroral arcs have been observed in the auroral ionosphere by optical, radar, and rocket observations, and called Enhanced Aurora. A striking resemblance between Enhanced and Artificial Aurora altitude profiles indicates that they are created by the above BPI process which results in the PTL.